THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND REACTION SPEED TO THE SERVICE SKILL OF STUDENTS IN SEPAK TAKRAW AT HIGH SCHOOL - Satria Octavian; Victor G Simanjuntak; M. Fachrurrozi Bafadal (Universitas Tanjungpura, 2023)
This study aims to determine whether there is a relationship between nutritional status and speed of reaction to the skill to serve in sepak takraw. The problem in this study was the technique of serving in sepak takraw is good, but there are some students who can not do it well, and the ball goes in or over the net and vice versa. The purpose of this study was to determine whether there is a relationship between nutritional status and reaction speed on the skill to serve in sepak takraw. This research is quantitative descriptive research with correlation research methods, and there are three variables studied, namely nutritional status, reaction speed, and service skill. This research was conducted by calculating the bivariate correlation and linear regression. The results of research on the relationship between nutritional status and speed of reaction to service skill. The results of the study: (1) there is no significant relationship with the low correlation coefficient rcount 0.394 < rtable 0.514 with a contribution of 15.5%. (2) there is no significant relationship with a very low correlation coefficient rcount 0.116 < rtable 0.514 with a contribution of 1.3%. (3) There is a moderate relationship between the correlation coefficient rcount (0.414) and rtable (0.514) with a contribution of 17.7%Â Keywords: Nutritional Status, Reaction Speed, Service Skill